Analysis of the association between anxiety and depression levels and oxidative stress levels (Annals of Medical Research, 2021)
Aim: There is a balance between reactive oxygen species (ROS) and antioxidant systems preventing them in the organism. In cases where this balance is impaired, molecular and cellular functions are negatively affected. Thiol-disulfide homeostasis (TDH) is also affected by this imbalance. It has been reported that the balance between oxidative and anti-oxidative systems is disrupted in individuals with psychiatric diseases such as anxiety and depression. Accordingly, it was aimed to determine the level of TDH in the serum of students who took the oral internship exam.Material and Methods: Volunteer fifth grade students of Medical Faculty, 19 male and 21 female, was included in the study. Of the students included in the study, Beck depression and Beck anxiety, albumin, ischemia-modified albumin (IMA), total thiol (SH + SS), native thiol (SH) and SS levels were measured and SS / SH + SS %, SH / SH + SS % and SS / SH % were calculated before and after the oral internship exam. These data were compared with the association between anxiety and depression level changes before and after the oral internship exam.Results: It was observed that the anxiety levels of the participants before the oral exam decreased in the period after the oral exam (p0.001). It was detected that the level of depression of the participants before the oral exam decreased after the oral exam (p0,05). Conclusion: Oral internship exam of Medical Faculty is a factor increasing anxiety and depression levels of the students. However, no association was found between oral internship exam and TDH parameters.
Keywords: Anxiety; depression; ischemia-modified albumin; native thiol; oral internship exam; total thiol